Rheumatic Fever and Rheumatic Heart Disease at the Department of Child Health, School of Medicine University of North Sumatera/ Dr. Pirngadi Hospital, Medan (1983 - 1985) - Mahruzzaman Naim; Guslihan Dasa Tjipta; A. Afif Siregar; Sahat Halim (Indonesian Pediatric Society, 1989)
A retrospective study on rheumatic fever and rheumatic heart disease in children was conducted at the Department of Child Health, Dr. Pirngadi Hospital Medon, during 1983 - 1985. The patients consisted of 43 females and 30 males. Most of the patients were over 12 years of age. Of the 73 patients there were 60 patients (82,19%) accompanied by valvular disorders. The most frequent major criteria of Jones found in this study were carditis and polyarthritis. Thirty one patients (42.46%) had functional status (NYHA) of grade II - IV, and 43 patients (58.90%) had cardiomegaly. The major ECG findings were enlargement of the atria or ventricles and first degree A V block. Compliance was only achieved in 25 (34.24%) cases. Rheumatic fever and rheumatic heart disease are still remain a challenge for the medical professionals in tireregion to cope with.